Ameliorative action of probiotics on the neurotoxicological effect of Aluminium chloride and D-galactose - Vaishali Lekchand Dasriya; Manorama Kumari; Soniya Ranveer; Pradip Behare; Shilpa Vij; Anil Kumar Puniya (Discover Toxicology)
Abstract This study aimed to investigate the protective effect of Limosilactobacillus fermentum NCDC701 against AlCl3 and D-galactose induced Alzheimer rat model. The dose of AlCl3 (50 mg/kg bodyweight) and D-galactose (100 mg/kg bodyweight) for 7 days induced oxidative stress such as amyloid plaque deposition, neuroinflammation, and reduction of neurotransmitters in the brain. In contrast, the supplementation of L. fermentum NCDC701 improved the neurotransmitter levels, antioxidants and anti-inflammatory cytokine IL-10, while decreased the amyloid peptide, pro-inflammatory cytokines, as well as LPS in colon and brain. The recovery in amyloid plaque deposition and tissue injury were also confirmed by the histopathological examinations. The supplementation of L. fermentum NCDC701 also improved the decreased expression levels of intestinal tight junction proteins, inhibited the up-regulation of p65, COX-2 and iNOS expression, and improved gut microbiota dysbiosis by increasing the Firmicutes: Bacteroidetes ratio. It also supported beneficial microflora (i.e. Oscillospira, Ruminococcus, Verrucomicrobia, Lactobacillus, and Prevotella), and suppressed the pathogenic microflora (i.e. Spirochaetes, Tenericutes, Prophyromonadaceae, Coprococcus, Clostridium, and Allobaculum) by increasing the concentration of butyrate and total short-chain fatty acids compared to the AlCl3 and D-galactose treated model. This finding provides insights into the effect of L. fermentum NCDC701 intervention on the gut–microbiome–brain axis and should assist future understanding of probiotics for improved host health.